2019
DOI: 10.5812/ijcm.67895
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T Polymorphism Is Associated with the Risk of Breast Cancer among Kurdish Population from Western Iran

Abstract: Background: The key enzyme of methylenetetrahydrofolate reductase (MTHFR) is involved in DNA biosynthesis and repair. Objectives: The role of MTHFR C677T polymorphism in susceptibility to breast cancer is controversial. Methods: In the present case-control investigation, 297 individuals consisted of 100 patients with breast cancer and 197 healthy women were studied for MTHFR C677T genotypes, using PCR-RFLP method. Results: The frequency of MTHFR TT genotype was 10% in patients and 3% in controls (P = 0.008). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Furthermore, in this study, the frequency of T allele of MTHFR C677T in patients was 54.5% vs.16.7% in controls with highly significant value (P= 0.001), indicating that the risk of breast cancer increases by 5.98 times in individual carrying the T allele. These results are supported by previous studies conducted on different populations as Indian and Moroccan suggesting that this polymorphism could be a therapeutic target for breast cancer (Waseem et al, 2016;Hardi et al, 2018;Rahimi et al, 2019). On the other hand, some previous case-control studies of: Mexican, north Indian, Turkish and Chinese population did not report any relation (Mir et al, 2008;Ramos-Silivia et al, 2015;Kaya et al, 2016;Song et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, in this study, the frequency of T allele of MTHFR C677T in patients was 54.5% vs.16.7% in controls with highly significant value (P= 0.001), indicating that the risk of breast cancer increases by 5.98 times in individual carrying the T allele. These results are supported by previous studies conducted on different populations as Indian and Moroccan suggesting that this polymorphism could be a therapeutic target for breast cancer (Waseem et al, 2016;Hardi et al, 2018;Rahimi et al, 2019). On the other hand, some previous case-control studies of: Mexican, north Indian, Turkish and Chinese population did not report any relation (Mir et al, 2008;Ramos-Silivia et al, 2015;Kaya et al, 2016;Song et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, it is observed that the haplotype T-C-G plays a high role in metastatic lymph nodal status with strong significant association (p= 0.003). In a support from (16,33) to our data, it is reported that there were tendencies for CRC patients with mutant genotypes to have more positive lymph nodes. However, other studies showed no significant difference in genotype distribution among different phases of metastatic lymph nodes (20).…”
Section: Discussionsupporting
confidence: 80%
“…Biochemical Genetics (2021) 59:367-397 A NOTE: Weights are from random effects analysis Overall (I-squared = 78.9%, p = 0.000) Naushad ( 2011) Lu (2015) Mir ( 2008) Huang ( 2014) Suzuki ( 2008) Rahimi (2019) Jiang-hua ( 2014) He ( 2014) Niu ( 2017) Hesari ( 2018) Chou (2006) Liu ( 2013) Lin ( 2004) Mohammadzadeh ( 2020) Yu ( 2007) Shrubsole ( 2004) Deligezer ( 2005) Kaya ( 2016) Pooja ( 2015) Hekim (2007) Hedayatizadeh ( 2017) Zhang ( 2015)…”
Section: Association Of the Mthfr A1298c Polymorphism With Breast Cancer Risk For Asiansmentioning
confidence: 99%
“…Biochemical Genetics (2021) 59:367-397 2015; Prasad and Wilkhoo 2011;Rahimi et al 2019;Sangrajrang et al 2010;Shrubsole et al 2004;Song et al 2016;Suzuki et al 2008;Waseem et al 2016;Weiner et al 2010;Weiwei et al 2014;Yu et al 2007;Zhang et al 2015) were found to be eligible based on inclusion criteria for the current meta-analysis. Figure 1 shows the flowchart of how the studies were identified and then selected step by step.…”
mentioning
confidence: 99%
See 1 more Smart Citation